Analisis Aktivitas Value Added dan Non Value Added Menggunakan Value Stream Mapping di Apotek Rawat Jalan - Andi Niartiningsih; Mene Paradilla; Nurfitriani Nurfitriani; Nurul Hidayah Nur; Muhammad Takwa (Universitas Pahlawan Tuanku Tambusai, 2025)
Value stream mapping is a tool in lean management used to identify activities that provide added value to customers and activities that do not provide added value (non value added) that can cause waste. The purpose of this study was to analyze value added and non value added activities using value stream mapping in the outpatient pharmacy of Haji Regional Hospital, Labuang Baji Regional Hospital and Makassar City Regional Hospital. This type of research is quantitative research using a sequential explanatory approach. The sample in this study used 110 prescription samples at the pharmacy. Data analysis in this study used univariate tests. The results showed that based on value stream mapping, the value added (VA) guarantee for finished drug prescriptions was 14.06 minutes (24.58%) and non value added (NVA) was 43.13 minutes (75.42%). Cash-based drug prescriptions VA 32.45 minutes (59.10%) and NVA 22.45 minutes (40.90%). Mixed drug prescriptions guaranteed VA 40.59 minutes (57.87%) and NVA 29.54 minutes (42.13%). The drug prescription became a cash mixture of VA 37.9 minutes (24.98%) and NVA 113.8 minutes (75.02%). The calculation of the ratio of value added to non-value added exceeded 30%, meaning it is not a lean enterprise. It is recommended that hospital management reduce waiting time, optimize drug stock, and train human resources to speed up the service process.